Modern treatment strategies in patients with vascular comorbidity Part 1. Correcting tissue energy deficiency - S. A. Rumyantseva; R. G. Oganov; E. V. Silina; V. A. Stupin; S. B. Bolevich; S. P. Svishcheva; A. S. Orlova; A. N. Komarov; V. A. Orlov; O. V. Abroskina; E. V. Eliseev; O. A. Sokhova; et al. (Кардиоваскулярная терапия и профилактика)
The first paper of the series on the treatment of patients with vascular comorbidity (VC) is focused on the role and therapeutic potential of the correction of free radical processes (FRP) as pathogenetic factors of multifocal vascular pathology. Aim. To analyse the effects of VC on the incidence and outcomes of cerebral stroke (S), in order to create therapeutic algorithms of FRP correction. Material and methods. This prospective study included 634 S patients. The following factors were analysed: pre-stroke disability due to various VC variants; VC effects on the clinical course, as well as in-hospital and post-discharge outcomes; and FRP specifics in various VC variants. Results. VC was registered in 97% of S patients; in 45,3%, it resulted in pre-stroke disability. FRP parameters, reflecting the progression of tissue energy deficiency, differed significantly in patients with coronary heart disease, myocardial infarction, atrial fibrillation, and diabetes mellitus. Based on these findings, the therapeutic algorithms for effective energy deficiency correction have been created. Conclusion. The analysis of pre- and post-stroke disability and prevention of repeat events in cardiovascular patients has demonstrated the need for a more active implementation of modern multidisciplinary preventive programs.